Confinamento de nanopartículas de ZrO2 e Cu em nanotubos de carbono para hidrogenação de CO2 em metanol - Iwasaki, Mariana Tiemi (Universidade Federal de São Carlos, 2024)
The CO2 hydrogenation reaction is a promising reaction because it enables the reduction of CO2 in the atmosphere and the utilization of H2 from renewable sources to produce useful chemical products for society. However, it is necessary to develop catalysts that are active, stable and selective to the desired product. Therefore, in this work, copper and zirconia catalysts supported on carbon nanotubes (CNT) were developed and their catalytic activity in the CO2 hydrogenation reaction to methanol was verified. The CNT catalysts were prepared by incipient impregnation and characterized by thermogravimetric analysis (TGA), RAMAN spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX), temperature programmed reduction in hydrogen (H2-TPR) and N2 physisorption. Catalytic tests were carried out in a fixed bed reactor, with catalyst reduction at 1 bar and 300°C in H2 for 1 hour, followed by the CO2 hydrogenation reaction at 30 bar and 250°C with a mixture of 3H2:1CO2 for 10 hours. TEM images showed metallic oxide particles of CuO and/or ZrO2 with size 1-10 nm dispersed inside the CNTs. In the catalytic tests, the 10Cu/CNT catalyst showed low CO2 conversion (~5%) and high CO selectivity (~70%), indicating that methanol is produced by the reverse water gas shift reaction and CO hydrogenation pathway. The Cu/Zr, Cu/Zr/CNT and Zr/Cu/CNT catalysts are highly selective to methanol (~85%), indicating that ZrO2 and the Cu-O-Zr interface are important active sites for methanol production. The Cu/Zr/CNT, Zr/Cu/CNT and Cu/Zr catalysts showed a period of instability in methanol selectivity of 4 h, corresponding to a transient state in which a structural change is occurring in the catalyst during the reaction at 30 bar and 250ºC, that makes them more selective to methanol. The Zr/Cu/CNT catalyst can be reused, but it takes around 6 hours to stabilize the methanol selectivity. In the catalytic stability test, the Zr/Cu/CNT catalyst remained stable during the 54.5 h reaction, ending the reaction with a CO2 conversion of 30% and methanol selectivity of 89%. Therefore, the Zr/Cu/CNT catalyst is active, stable and methanol selective.
Confinement of ZrO2 and Cu nanoparticles into carbon nanotubes for hydrogenation of CO2 to methanol
Keywords: Hidrogenação do CO2; Metanol; CNT; Cobre; Zircônia; CO2 hydrogenation; Methanol; Copper; Zirconia; ENGENHARIAS::ENGENHARIA QUIMICA